STUDI NUMERIK ALIRAN 3D INTERAKSI AIRFOIL DAN PLAT DATAR - Rachman, Arfidian; Yuana Dewi, Arfirta; Effendi, Asnal (Jurnal Teknologi dan Vokasi, 2025)
The effect of secondary flows in the wing-body configuration on aircraft—that is, the presence of wingtip-vortex on the tip region and the creation of multiple elements of the vortex flow on the endwall region—is the basis for studies of the existence of these secondary flow structures. These two factors combined will obstruct the main flow. The presence of this blocking effect will have an impact on the lift and drag aerodynamics, which directly impacts the wing's efficacy and efficiency. The saddle point's position shifting toward the pressure side is a phenomenon that can be seen in the endwall area. On the other hand, the area of maximum pressure on the lower surface travels towards the press side, and the movement of the minimum pressure point on the upper surface is found to be closer to the leading edge based on the isobar contour. The study will be carried out experimentally on a flat plate model with a wing shape change with an angle of attack variation (α) = 0o.